2009
DOI: 10.1093/brain/awp037
|View full text |Cite
|
Sign up to set email alerts
|

The clinical profile of right temporal lobe atrophy

Abstract: Frontotemporal lobar degeneration is currently associated with three syndromic variants. Disorders of speech and language figure prominently in two of the three variants, and are associated with left-sided frontotemporal atrophy. The detailed characterization of these syndromes contrasts with the relative paucity of information relating to frontotemporal lobar degeneration primarily affecting the right cerebral hemisphere. The objective of this study was to identify the clinical profile associated with asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
299
4
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(337 citation statements)
references
References 38 publications
(46 reference statements)
29
299
4
5
Order By: Relevance
“…The findings are consistent with previous work showing reduced autonomic reactivity in bvFTD and nfvPPA18, 26 and preserved autonomic reactivity in svPPA 31. The present work goes further in demonstrating a physiological basis for differentiating subsyndromes within the canonical diagnostic grouping of bvFTD: although a distinct syndrome of rtvFTD has been proposed on neuroanatomical and clinical grounds,2, 3 these are to a degree arbitrary given the extensive clinico‐anatomical overlap between patients and without mechanistic grounding. Autonomic profiling might establish a principled neurobiological rationale for subclassifying bvFTD, which has long presented nosological difficulties on account of its marked phenotypic and pathological heterogeneity.…”
Section: Discussionsupporting
confidence: 92%
“…The findings are consistent with previous work showing reduced autonomic reactivity in bvFTD and nfvPPA18, 26 and preserved autonomic reactivity in svPPA 31. The present work goes further in demonstrating a physiological basis for differentiating subsyndromes within the canonical diagnostic grouping of bvFTD: although a distinct syndrome of rtvFTD has been proposed on neuroanatomical and clinical grounds,2, 3 these are to a degree arbitrary given the extensive clinico‐anatomical overlap between patients and without mechanistic grounding. Autonomic profiling might establish a principled neurobiological rationale for subclassifying bvFTD, which has long presented nosological difficulties on account of its marked phenotypic and pathological heterogeneity.…”
Section: Discussionsupporting
confidence: 92%
“…The association of modality-specific PP, mild object visual agnosia, and early behavioural changes with insidious onset and gradual progression, in presence of normal phosphorylated tau and beta-amyloid in CSF, might be consistent with a diagnosis of prosopagnosic variant of FTD (Neary et al, 1998), more recently defined as right-temporal variant of FTD (rtFTD; Chan et al, 2009;Josephs et al, 2009;Miller et al, 1993).…”
Section: Discussionmentioning
confidence: 84%
“…Actually, current clinical diagnostic criteria (Neary et al, 1998) consider PP with insidious onset and gradual progression, often associated to associative agnosia, as the hallmark of the prosopagnosic variant of frontotemporal dementia (FTD) (Neary et al, 1998), more recently defined right-temporal variant (rtFTD; Chan et al, 2009;Josephs et al, 2009;Miller et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some patients with semantic dementia ($30%) present initially with greater atrophy in the right anterior temporal lobe, and these patients often have greater social-emotional deficits along with prosopagnosia (Chan et al, 2009;Hodges et al, 2010;Irish et al, 2013). Patient-specific neurodevelopmental factors likely contribute to the selective vulnerability of neural regions and networks to progressive degeneration (Rogalski et al, 2008;Spreng et al, 2010;Miller et al, 2013), and may account for some of the variability observed in the atrophy patterns of patients with svPPA.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%